2017
DOI: 10.1002/pat.4088
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of glass fiber–reinforced polyethylene terephthalate/linear low density polyethylene (GFPET/LLDPE) composites

Abstract: Polyethylene terephthalate (PET) was melt blended with linear low density polyethylene (LLDPE) and subsequently compounded with glass fibers (GF) as reinforcements at percentages ranging from 15 to 45 wt% of LLDPE and 5 to 30 wt% of GF. Thermal, morphological, and mechanical properties of the prepared composites were investigated. It was found that compounding PET/LLDPE blends with GF would be beneficial in producing composites that are thermally stable with good mechanical properties. For example, the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The technical performance of PET, especially in terms of thermal stability and thermo-mechanical resistance, allow one to use it as a potential replacement for polyamides (PA) for those applications in which polyolefins typically cannot be used due to their poor thermal resistance [ 15 ]. Several studies have reported on the manufacturing of injection-molded, PET-based, fiber-reinforced composites [ 15 , 16 , 17 , 18 ]. For example, Alqaflah et al [ 16 ] prepared glass-fiber composites based on blends of PET and LLDPE, demonstrating the positive contribution of LLDPE in improving impact strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical performance of PET, especially in terms of thermal stability and thermo-mechanical resistance, allow one to use it as a potential replacement for polyamides (PA) for those applications in which polyolefins typically cannot be used due to their poor thermal resistance [ 15 ]. Several studies have reported on the manufacturing of injection-molded, PET-based, fiber-reinforced composites [ 15 , 16 , 17 , 18 ]. For example, Alqaflah et al [ 16 ] prepared glass-fiber composites based on blends of PET and LLDPE, demonstrating the positive contribution of LLDPE in improving impact strength.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the manufacturing of injection-molded, PET-based, fiber-reinforced composites [ 15 , 16 , 17 , 18 ]. For example, Alqaflah et al [ 16 ] prepared glass-fiber composites based on blends of PET and LLDPE, demonstrating the positive contribution of LLDPE in improving impact strength. Arencón et al [ 17 ] studied the thermal and mechanical properties of short glass-fiber-reinforced PET, focusing on the influence of three of the variables involved in the injection-molding process: mold temperature, holding pressure time, and closed mold time.…”
Section: Introductionmentioning
confidence: 99%
“…2 As one of the five major general engineering plastics, it was also used in electronic and electrical, automotive and instrumentation fields. 3,4 In addition to demanding high mechanical properties of materials, these industries also had strict requirements on flame retardant and safety performance. However, the limit oxygen index (LOI) of PET was only about 21%, and produced a large number of molten droplets during combustion, 5 which limits the development speed to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recycling of these used bale wraps to value-added products could be benecial for farmers as well as for dairy and cattle industries for the time being. Several research groups have attempted to utilize LLDPE to fabricate PET based blends [24][25][26][27][28][29][30] or multilayer lms. Incorporation of LLDPE in PET may enhance the engineering aspect of the extrusion process, such as mold releasability, 31 melt processability, reducing bulk density as well as improving toughness etc.…”
Section: Introductionmentioning
confidence: 99%